2022
DOI: 10.3390/ijerph192315702
|View full text |Cite
|
Sign up to set email alerts
|

Group Segmentation as a Strategy for Implementing the Intervention Programme in Emotional Education for Infant and Primary Teachers

Abstract: Emotional intelligence is a key social skill for teachers. The teaching profession requires programmes that are geared towards emotional education that will enable teachers to develop emotional intelligence in order to foster their general well-being. The aims of this paper were: firstly, to test the effectiveness of the programme in emotional education implemented through group segmentation based on teachers’ sociodemographic and work profile factors, and secondly, to ascertain whether there were any signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…However, while in early childhood teachers the association between self-esteem and eudaimonic wellbeing was found to be strong, in primary school teachers’ self-esteem was found to be more closely related to life satisfaction, as noted in previous studies [ 29 , 53 ]. This indicate that the greatest link in the dynamics of emotional wellbeing in teachers is represented by the feeling of subjective happiness and satisfaction with life; in infant teachers the pursuit of eudaimonic wellbeing is related to self-esteem, while in primary school teachers self-esteem is less closely related to eudaimonic wellbeing than to satisfaction with life [ 2 , 39 , 54 ]. Therefore, our study indicates that there is greater understanding of philosophy of life (eudaimonic welfare) in early childhood education teachers; in other words, preschool teachers present greater spiritual and existential understanding than EP teachers [ 11 , 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while in early childhood teachers the association between self-esteem and eudaimonic wellbeing was found to be strong, in primary school teachers’ self-esteem was found to be more closely related to life satisfaction, as noted in previous studies [ 29 , 53 ]. This indicate that the greatest link in the dynamics of emotional wellbeing in teachers is represented by the feeling of subjective happiness and satisfaction with life; in infant teachers the pursuit of eudaimonic wellbeing is related to self-esteem, while in primary school teachers self-esteem is less closely related to eudaimonic wellbeing than to satisfaction with life [ 2 , 39 , 54 ]. Therefore, our study indicates that there is greater understanding of philosophy of life (eudaimonic welfare) in early childhood education teachers; in other words, preschool teachers present greater spiritual and existential understanding than EP teachers [ 11 , 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relevance of wellbeing in teachers and although education and psychological wellbeing are considered fundamental variables, no research has been found that analyses psychological wellbeing from an educational perspective. In addition, research on psychological wellbeing in teachers is scarce, although recent research suggests that the profile of teachers in Early and Primary Education may be different [ 39 ].…”
Section: Research Targetsmentioning
confidence: 99%
“…A mayor comprensión, mayor percepción, regulación emocional y mejores niveles de competencias instruccionales, comunicativorelacionales y socioemocionales. A mayor regulación, mayor percepción, comprensión emocional y mejores niveles de competencias instruccionales, comunicativo-relacionales y socioemocionales (Carbonero-Martín et al, 2022). De la misma manera a mejores niveles de competencias instruccionales, comunicativo-relacionales y socioemocionales, mejores niveles de percepción, comprensión y regulación emocional (Arteaga-Cedeño, 2023).…”
Section: Discussionunclassified
“…The instrument integrates three dimensions that measure different aspects of emotional intelligence (emotional attention, emotional clarity, and emotional repair). The TMMS-24 has been used in previous studies (Arteaga-Cedeño et al, 2022;Carbonero-Martín et al, 2022;Redondo-Rodríguez et al, 2023). In this study, emotional intelligence measured as the final score obtained on the TMMS-24 (24-120 points) was used.…”
Section: Instrumentsmentioning
confidence: 99%